Formation and evolution of large-scale structures from the perspective of halo models - Silva, Emanuelly; Nunes, Rafael C. (Cadernos de Astronomia, 2025)
The current era of large-scale structure research, driven by projects such as DESI, Euclid, and LSST, demands efficient methods for modeling and interpreting vast datasets. The matter power spectrum, P(k, z), is a central statistical estimator in these efforts, but its modeling on nonlinear scales remains an ongoing challenge in the literature. In this context, halo models provide a powerful approach by associating the distribution of matter with halos of different masses. Widely used in tools such as HALOFIT and HM-CODE, these models play a fundamental role in data analysis and cosmological parameter inference. This article aims to provide an introductory and didactic resource that reviews the essential components of halo models, highlighting their advantages, such as flexibility beyond the standard ΛCDM model, and their impact on galaxy property predictions, observational studies, and theoretical modeling. The review is presented in a clear and accessible manner, aiming to introduce this approach, which will become increasingly indispensable in modern cosmology.
Keywords: power matter spectrum; large scale structure; halo models; cosmological parameter inference